2016
DOI: 10.1186/s13071-016-1920-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycoplasma haemocanis, Mycoplasma haematoparvum, Mycoplasma suis and other vector-borne pathogens in dogs from Córdoba and Santa Fé, Argentina

Abstract: BackgroundIn Argentina, only very few reports are available for canine tick-borne diseases where most are related to parasitic diseases. The objective of this survey was to investigate the prevalence of tick-borne pathogens in 70 dogs from Santa Fé and Córdoba, Argentina.MethodsMicroscopic blood smear examination as well as polymerase chain reaction (PCR) amplification using species-specific markers of Anaplasma, Babesia, Bartonella, Borrelia, Ehrlichia, Francisella, Mycoplasma (hemotropic group) and Rickettsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
2
18
1
2
Order By: Relevance
“…Evidences of infection with some of the pathogens studied here were found in other little populated areas, like in a range of jackal and fox species from northern Africa (Maia et al, 2014) and in arctic foxes (Mascarelli et al, 2016). In consequence, we cannot discard that the pathogens studied here were brought to Patagonia by dogs during the last two centuries.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Evidences of infection with some of the pathogens studied here were found in other little populated areas, like in a range of jackal and fox species from northern Africa (Maia et al, 2014) and in arctic foxes (Mascarelli et al, 2016). In consequence, we cannot discard that the pathogens studied here were brought to Patagonia by dogs during the last two centuries.…”
Section: Discussionsupporting
confidence: 52%
“…Hemoplasma DNA was detected in some foxes and in a remarkable proportion of the flea pools analysed. Mycoplasma haemocanis infects dogs worldwide (Shapiro et al, 2017; Soto et al, 2017; Aktas and Ozubek, 2018), including Argentina (Mascarelli et al, 2016). As many as 77% of dogs from northern Argentina were infected with hemoplasmas; M. haemocanis was the most prevalent species (Mascarelli et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…All dogs included in the Control Group (exposed, without CME signs) were negative both by PCR and the SPEED  EHRLI serological assay. These findings coincide with previous reports from other authors in which no DNA of E. canis was detected in samples obtained from clinically healthy dogs (Cicuttin et al 2015, Mascarelli et al 2016. However, some studies carried out in Buenos Aires city have reported a prevalence value of 13.5 for Anaplasma platys (Cicuttin et al 2011(Cicuttin et al , 2014a.…”
Section: Discussionsupporting
confidence: 91%
“…Cicuttin et al (2016) in samples of canines with symptoms compatible with EMC of the Metropolitan Area of Buenos Aires described a prevalence of 6.7% (15/223) to E. canis. On the other hand, in clinical healthy dogs from Buenos Aires, San Luis, Córdoba and Santa Fe, only the presence of Anaplasma platys DNA, but not E. canis, was demonstrated (Cicuttin et al 2011, 2014a, 2014b, 2017a, Mascarelli et al 2016. Serological studies published in our country are scarce.…”
Section: Introductionmentioning
confidence: 73%
“…Babesiosis due to B. vogeli has been described in three dogs from Buenos Aires [12, 251] and detected in 10% (2/21) and 6.8% (3/41) of shelter dogs from Córdoba and Santa Fé, respectively, by molecular methods [252]. Large piroplasms have furthermore been detected in 0.2% of tested animals in a large canine survey with more than 16,000 dogs [12, 251].…”
Section: Country Filesmentioning
confidence: 99%